DESIGN OF UNMANNED GRENADE TAMER PROTOTYPE WITH WIRELESS CONTROL - Aris Tri Ika Rahmadi; Ayip Rivai Prabowo; Ali Mashudi; Luqman Arif (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Puslatdiksarmil is a military training and basic education center. To support the trainer in securing the grenadeduring the grenade throwing exercise, the author made